COMPONENTS OF SELF-KNOWLEDGE OF BACHELORS AND MASTERS (Psychology Travelogs, 2022)
The article presents the results of a study of the structure of self-knowledge. Such components of self-knowledge as self-perception, reflection, self-assessment, self-observation and self-analysis were theoretically identified and substantiated. The results of an empirical study of these components in a sample of students at the bachelor's and master's levels were presented. The following methods were used: «Diagnosis of reflection» (A. Karpov), «Verbal self-esteem», «Test of twenty statements» (by M. Kuhn and T. McPartland) for the study of self-perception and self-reports of higher education students for research self-observation and introspection.It was found that most of the students have low self-esteem, rather narrow self-perception. The level of ability to reflect, self-analysis and self-observation are mostly at a medium level, but also need development and correction.A number of measures have been proposed for the development of self-knowledge in applicants for higher education at the bachelor’s and master’s levels, including: conducting special trainings for the development of both individual components of self-knowledge and complex self-knowledge trainings; tasks for self-analysis and self-observation in the context of professionally oriented disciplines (thematic and complex self-analyzes; diaries of self-observation, reflections, self-analysis, self-evaluation; self-observation with the help of photography and video, etc .; work in pairs «observer and observіng» etc.); creative activity and analysis of its products; individual work with a psychologist; participation in the work of psychological groups (developmental, psycho-correctional, psychotherapeutic, educational-therapeutic, etc.); raising the general cultural level through reading, attending concerts, art exhibitions, museums, traveling, etc.There are such prospects for further work on this problem in the study of the relationship of self-knowledge with individual-typological personality traits, the level of formation of arbitrary self-government and self-regulation.
Keywords: self-knowledge; self-perception; reflection; self-assessment; self-observation; self-analysis